Design, synthesis, and biological evaluation of novel N 4 -substituted sulfonamides: acetamides derivatives as dihydrofolate reductase (DHFR) inhibitors - Essam M. Hussein (BMC Chemistry, 2019)
Abstract Background Sulfonamide derivatives are of great attention due to their wide spectrum of biological activities. Sulfonamides conjugated with acetamide fragments exhibit antimicrobial and anticancer activities. The inhibition dihydrofolate reductase (DHFR) is considered as one of the most prominent mechanism though which sulfonamide derivatives exhibits antimicrobial and antitumor activities. Results In this study, a new series of 2-(arylamino)acetamides and N-arylacetamides containing sulfonamide moieties were designed, synthesized, characterized and assessed for their antimicrobial activity and screened for cytotoxic activity against human lung carcinoma (A-549) and human breast carcinoma (MCF-7) cell lines. A molecular docking study was performed to identify the mode of action of the synthesized compounds and their good binding interactions were observed with the active sites of dihydrofolate reductase (DHFR). Conclusion Most of the synthesized compounds showed significant activity against A-549 and MCF-7 when compared to 5-Fluorouracil (5-FU), which was used as a reference drug. Some of these synthesized compounds are active as antibacterial and antifungal agents.